HOW ATMOSPHERIC CUES IN A VIRTUAL REALITY FASHION STORES AFFECT THE SENSE OF PRESENCE - Crespo, M.; Loureiro, S. M. C.; Guerreiro, J. (2019 Global Fashion Management Conference at Paris, 2019)
Virtual Reality is characterized by its levels of Immersion in a new world (e.g., Eroglu et al., 2001; Bhatt, 2004). Immersion is strongly related to the concept of flow, since involves a psychological state of isolation from the real world (Witmer & Singer, 1998; Bhatt,2004). This is strongly related to the concept of Flow. Thus, a total sense of involvement of a consumer in a certain experience exists, resulting in an experience unlike any other, and without unexpected distractions (Nah, Eschenbrenner & DeWester, 2011; Loureiro et al., 2018). Indeed, Mikropoulos (2006) claims that immersion causes a feeling of total presence (telepresence). However, there is a gap in literature liked to the lack of studies dealing with the way atmospheric cues of the fashion store influences presence. By atmospheric cues intended as “the conscious designing of space to create certain buyer effects” (Kotler, 1974, p. 50). The definition reflects the effort of creating retail environments that are intended to produce certain emotional effects on the buyer. Emotions that could develop and intensify the sense of presence. Thus, the aim of the current study is to explore how atmospheric cues in virtual reality fashion stores affect the sense of presence.